Sustainable Innovations in Mineral Fertilizer Production: Progress and Challenges - Abdurazova, Perizat; Yegemberdiyeva, Saltanat; Nazarbek, Ulzhalgas; Raiymbekov, Yerkebulan (Pandawa Institute, 2026)
This study provides a comprehensive analysis of recent advancements in the production of nitrogen, potash, and phosphorus fertilizers, focusing on innovations that enhance both efficiency and environmental sustainability. Key technological breakthroughs discussed include low-energy ammonia synthesis through electrochemical and plasma-assisted processes, phosphate recovery from municipal and industrial wastewater, and the use of potassium-bearing industrial by-products such as mica, feldspar, and fly ash. The review highlights the development of green synthesis methods that minimize the environmental footprint and offer cost-effective routes to utilize secondary raw materials. Special attention is paid to the integration of circular economy principles and zero-waste approaches in fertilizer production, including the transformation of phosphogypsum and sludge into valuable fertilizer components. Moreover, the potential application of nanotechnology for nutrient delivery optimization and precision farming techniques for improving fertilizer use efficiency are critically examined. This paper provides a detailed overview of current trends and future perspectives in sustainable mineral fertilizer production. By emphasizing innovative strategies and emerging technologies, the article underlines the importance of environmentally responsible approaches to support global food security while preserving ecological balance.